Acute Changes in Community Violence and Increases in Hospital Visits and Deaths From Stress-responsive Diseases. Issue 5 (September 2018) - Ahern, Jennifer; Matthay, Ellicott C.; Goin, Dana E.; Farkas, Kriszta; Rudolph, Kara E.
Abstract : Background: Community violence may affect a broad range of health outcomes through physiologic stress responses and changes in health behaviors among residents. However, existing research on the health impacts of community violence suffers from problems with bias. Methods: We examined the relations of acute changes in community violence with hospital visits and deaths due to stress-responsive diseases (mental, respiratory, and cardiac conditions) in statewide data from California 2005–2013. The community violence exposure was measured as both binary spikes and continuous acute changes. We applied a combined fixed-effects and time-series design that separates the effects of violence from those of community- and individual-level confounders more effectively than past research. Temporal patterning was removed from community violence rates and disease rates in each place using a Kalman smoother, resulting in residual rates. We used linear regression with place fixed-effects to examine within-place associations of acute changes in community violence with residual rates of each outcome, controlling for local time-varying covariates. Results: We found acute increases in hospital visits and deaths due to anxiety disorders (0.31 per 100, 000; 95% confidence interval [CI] = 0.02, 0.59), substance use (0.47 per 100, 000; 95% CI = 0.14, 0.80), asthma (0.56 per 100, 000; 95% CI = 0.16, 0.95), and fatal acute myocardial infarction (0.09 per 100, 000; 95% CI = 0.00, 0.18) co-occurring with violence spikes. The pattern of findings was similar for the exposure of continuous acute violence changes. Conclusions: Although the associations were small, the identified increases in stress-responsive conditions suggest the possibility of health impacts of acute changes in community violence. Abstract : Supplemental Digital Content is available in the text.